Investigation of Knowledge, Attitude and Practice of Personal Protection Among Different Types of Workers Returning to Work Under COVID-19 Epidemic - Fan, Zhaoya; Mou, Yuanlin; Cheng, Rui; Zhao, Yong; Zhang, Fan (Frontiers in Public Health, 2021)
Background: Since the outbreak of the coronavirus disease 2019 (COVID-19) epidemic, it has had a significant negative impact on the economy and employment. The orderly resumption of work and production is an important factor in reducing the impact of the COVID-19 and an important guarantee of social and economic stability. The study aimed to investigate the knowledge, attitudes, and practice (KAP) of people returning to work about personal protection under the COVID-19 epidemic. Methods: During March 2020, based on WeChat, QQ and other internet platforms, online questionnaire survey was conducted by the convenience sampling method. SPSS version 20.0 (SPSS, Inc., Chicago, IL, USA) was used for statistics analysis. Descriptive statistics and multiple linear regression analyses were conducted to analyze the data. Results: A total of 302 valid questionnaires was collected, and the valid response rate was 86.7%. About knowledge, people who return to work had the highest awareness rate of safe communication distance and the lowest awareness rate of exposure risk levels in different workplaces. The average scores of respondents in different occupations were higher than 95 in terms of personal protective attitude. In terms of practice, the average scores of respondents in different occupations were higher than 90 points. Multiple linear regression results showed that education and place of residence were the influencing factors of knowledge, while gender was the influencing factor of practice. Conclusion: The awareness of prevention and control among the 302 participants was good. There were differences in personal protection knowledge among different occupational groups, but there were no differences in attitude and practice. Our findings were of great significance to improve the pertinence of COVID-19 prevention programs.